2009
DOI: 10.3892/or_00000403
|View full text |Cite
|
Sign up to set email alerts
|

p12CDK2-AP1 is associated with tumor progression and a poor prognosis in esophageal squamous cell carcinoma

Abstract: Abstract. p12 CDK2-associating protein 1 (p12 CDK2-AP1 ) is a growth suppressor that negatively regulates cyclin-dependent kinase 2 (CDK2) activities. In addition, p12CDK2-AP1 has also been shown to interfere in DNA replication. A reduction of p12 CDK2-AP1 expression is known to be a negative prognostic indicator in patients with oral squamous cell carcinoma. To elucidate the role of p12 CDK2-AP1 expression in esophageal squamous cell carcinoma (ESCC), we immunohistochemically examined the expression of p12 CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a study, aberrant promoter methylation of the CHFR gene was reported in patients with OSCC, while the gene was methylated minimally in the surrounding normal mucosa and no methylation was observed in the CHFR promoter in a healthy cohort (Baba et al 2009; Toyota et al 2003). …”
Section: Studies Of Individual Genesmentioning
confidence: 99%
“…In a study, aberrant promoter methylation of the CHFR gene was reported in patients with OSCC, while the gene was methylated minimally in the surrounding normal mucosa and no methylation was observed in the CHFR promoter in a healthy cohort (Baba et al 2009; Toyota et al 2003). …”
Section: Studies Of Individual Genesmentioning
confidence: 99%